Potential area of micro-irrigation and its outreach across Indian states - KISHORE, P; CHAND, S; SRIVASTAVA, S K (The Indian Journal of Agricultural Sciences, 2022)
Indian agriculture is predominantly dependent on groundwater and consumes nearly 89% of its total groundwater draft. With recurrence of drought and faster depletion of groundwater resources in recent past, micro-irrigation technology has emerged to play crucial role in managing irrigation water demand and sustaining food security. The policy makers, recognising gravity of water scarcity across the Indian states, have focussed water policy pivotal to micro-irrigation. So, present study aims to estimate potential area across Indian states that are suitable for adoption of micro-irrigation. For estimation, sources of irrigation and crop suitability for micro-irrigation primarily under drip and sprinkler irrigation are considered across the states for year 2018–19. Based on different combinations of irrigation sources, estimate shows that country endows an area of 72–78 million ha on which micro-irrigation can be adopted. At country level, micro-irrigation penetration to our estimates ranges from 14.71–15.81% in recent years. Further, location coefficient reveals that concentration of micro-irrigation has improved over the years, however noticeable variation exists across the states. The states with dedicated agencies to improve micro-irrigation adoption like Andhra Pradesh and Gujarat, show higher penetration. However, the state like Punjab that faces water scarcity has low penetration of micro-irrigation. Therefore, there is need to have state-specific schemes to scale up micro-irrigation area for better trade-off between environmental sustainability and food security.